Gnvq intermediate business - Clarke, Gill.; Lewis, Roger; Latham, Richard ([S.l.] : Nelson Thornes Ltd, 1993)
Designed specially for GNVQ Intermediate Business, this textbook provides full coverage of the the four mandatory units and also much of the optional unit content. It is also suitable for NVQs in Business Administration and the BTEC First course. Each chapter covers the theory through realistic business assignments, and there are practical exercises throughout.
Keywords: business